Social Media Awareness among Farmers in Haryana: An Age-wise Comparative Analysis - Mishra, Ayush; Singh, Kuldeep; Singh, Jogender; Malik, Joginder Singh (Indian Journal of Extension Education, 2026)
The study measured farmers’ social media awareness and compared the awareness across different age groups in Haryana. A descriptive and analytical research design was employed, and data were collected from 240 farmers, equally divided into three age groups and selected through multi-stage stratified random sampling from eight villages across two districts. Data were gathered using a structured interview schedule, and analysis was conducted using statistical tools including independent sample t-test, Pearson product-moment correlation and multiple linear regression. The results showed that a majority of respondents possessed a medium level of social media awareness. Further, the young farmers exhibited significantly higher awareness compared to other age groups. Also, it was observed that farmers were largely aware of social media for information sharing, communication, and entertainment, but awareness regarding marketing applications remained low. Socio-economic variables such as age, education, extension participation and contact and scientific orientation emerged as the strongest predictors of social media awareness. The study proposes targeted training programmes on digital literacy and institutional linkage to enhance farmers’ awareness and professional use of social media platforms.